MoodJumper: An Exploration of Game Interface Preferences in Users With/Out Mood Disorder - Baghaei, Nilufar; Hach, Sylvia; Liang, Hai-Ning; Brucker, Marvin (Frontiers in Public Health, 2019)
Mental health conditions pose a major challenge to healthcare providers and society at large. The World Health Organization predicts that by 2030 mental illnesses will be the leading disease burden globally. Mental health services are struggling to meet the needs of users and arguably fail to reach large proportions of those in need. According to New Zealand Mental Health Foundation, one in five will experience a serious mood disorder, including depression, at some time in their life. Games for Health including those supporting mental health have recently gained a lot of attention. However, game interface preferences for users with a history of mental health conditions have not been systematically studied, making it difficult to determine what game features may attract and further engage users affected by mental health conditions. We present MoodJumper, a prototype Android mobile game, which enables players to jump to the top of the level by steering the avatar from platform to platform, gradually gaining height and collecting coins on the way up. We conducted a preliminary study (n = 25), in which participants were able to modify different settings of the game (background color, dark/light, character movement, gender, and music), while their gaming behavior was tracked. The results show that regardless of self-reported history of mood disorder, the majority of participants prefer the dark and colored layout setting and there were no differences in gaming variables including session duration and high scores. This represents a first indication that history of mood disorder does not affect user preferences for game interface settings. It will be important to follow up with data on users currently affected by low mood. Systematic study of game interface preferences in users with mood disorder constitutes a vital step in being able to harness the potential power of games for supporting mental health.